Indeks Kepuasan Masyarakat (IKM) pada Kantor Camat Kecamatan Sarolangun Kabupaten Sarolangun - Dahmiri Dahmiri (STIE Malangkucecwara, 2014)
This study aims to analyze public satisfaction index at Kantor Camat Kecamatan Sarolangun Kabupaten Sarolangun. This study took a sample of 150 respondents by Kepmen PAN No. 25 / KEP / M.PAN / 2/2004. The method used in this research using mixed qualitative descriptive study to determine community satisfaction index of services in the Kantor Camat Kecamatan Sarolangun Kabupaten Sarolangun. To measure the level of satisfaction of the people use the value of Community Satisfaction Index (HPI), which is calculated using the weighted average value of each element of the service. The results showed that there are 3 (three) dimensions in both categories, namely: dimensions service procedures, the ability of service personnel and environmental safety. While the dimensions are not good category there are 2 (two), namely fairness of service and assurance service charge. The dimensions in the unfavorable category there are nine (9) that the terms of service, clarity of service personnel, service personnel discipline, responsibility for care workers, speed of service, courtesy and friendliness of the clerk, the reasonableness of the cost of service, service schedule certainty, and comfortable environment.